Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1097/psy.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Crux of Autonomic Dysfunction in Posttraumatic Stress Disorder: Whether Chronic or Situational Distress Underlies Elevated Heart Rate and Attenuated Heart Rate Variability

Abstract: Objective Posttraumatic stress disorder (PTSD) has been linked to elevated heart rate (HR) and reduced heart-rate variability (HRV) in cross-sectional research. Using ecological momentary assessment (EMA) and minute-to-minute HRV/HR monitoring, we examined whether cross-sectional associations between PTSD symptom severity and HRV/HR were due to overall elevations in distress levels or to attenuated autonomic regulation during episodes of acute distress. Methods Two hundred nineteen young adults (18–39 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 22 publications
(20 reference statements)
2
28
0
2
Order By: Relevance
“…Research has linked hostility in individuals with PTSD to physiological hyperarousal (Beckham et al, 2009, 2002; Vrana et al, 2009), and improved arousal regulation has been found to be the one of the primary mechanisms of change in anger management therapy for veterans with PTSD (Mackintosh et al, 2014a, 2014b). Considered in the context of these prior studies, our findings may suggest that directly targeting the PTSD-related physiological arousal (Beckham et al, 2009, 2002; Dennis et al, 2016, 2017; Mackintosh et al, 2014a, 2014b; Vrana et al, 2009) and hostile cognitions (Van Voorhees et al, 2016) that contribute to irritability and anger may be an important part of a holistic approach to minimizing the functional impact of the disorder. Current empirically support therapies specifically target the avoidance symptoms that are understood to maintain PTSD (Cahill et al, 2003; Foa et al, 2006; Resick et al, 2010), while less attention is given to directly targeting physiological arousal and hostile interpersonal attributions cued by trauma triggers.…”
Section: Discussionmentioning
confidence: 82%
“…Research has linked hostility in individuals with PTSD to physiological hyperarousal (Beckham et al, 2009, 2002; Vrana et al, 2009), and improved arousal regulation has been found to be the one of the primary mechanisms of change in anger management therapy for veterans with PTSD (Mackintosh et al, 2014a, 2014b). Considered in the context of these prior studies, our findings may suggest that directly targeting the PTSD-related physiological arousal (Beckham et al, 2009, 2002; Dennis et al, 2016, 2017; Mackintosh et al, 2014a, 2014b; Vrana et al, 2009) and hostile cognitions (Van Voorhees et al, 2016) that contribute to irritability and anger may be an important part of a holistic approach to minimizing the functional impact of the disorder. Current empirically support therapies specifically target the avoidance symptoms that are understood to maintain PTSD (Cahill et al, 2003; Foa et al, 2006; Resick et al, 2010), while less attention is given to directly targeting physiological arousal and hostile interpersonal attributions cued by trauma triggers.…”
Section: Discussionmentioning
confidence: 82%
“…The present paper builds on prior publications from on a broader study examining health risks associated with PTSD in young adults (6, 1721). For the present analysis, potential participants were 211 young adults (18–39 years old), 93 of whom (44%) met DSM-IV criteria for PTSD.…”
Section: Methodsmentioning
confidence: 97%
“…Moreover, PTSD measure (clinical interview v. self-report) was examined. PTSD symptom severity might be connected to diminished LF-HRV and HF-HRV in acute distress (Dennis et al, 2016 ), thus constituting potential moderators. Furthermore, medication use and comorbidities were examined as moderators.…”
Section: Methodsmentioning
confidence: 99%
“…Alterations in arousal may also change cardiovascular stress activity and reactivity. This can lead to either increased or blunted responsiveness of individuals with PTSD to challenging and stressful tasks (Cohen et al, 2000 ; Dennis et al, 2016 ; Jovanovic, Norrholm, Sakoman, Esterajher, & Kozarić-Kovačić, 2009 ).…”
Section: Introductionmentioning
confidence: 99%